Seed security and resilience: Gender perspectives - McGuire, Shawn (Food and Agriculture Organization of the United Nations, 2019)
Presented by Shawn McGuire (Food and Agriculture Organization / FAO) on 21 November 2019, as part of the webinar "Gender dynamics in formal seed systems in Sub-Saharan Africa and worldwide lessons". The webinar was co-organized by the CGIAR Collaborative Platform for Gender Research and CGIAR Research Program on Maize.